The concept of “labour / mehnat” in russian and uzbek paremiology: a linguocultural analysis - Meyliyeva, Malika; Azizova, Nasiba Bakhritdinovna (The Lingua Spectrum, 2026)
The article investigates the concept of “labour / mehnat” from a linguocultural perspective based on Russian and Uzbek proverbs and sayings. The etymology of key lexical units (trud, rabota, mehnat, ish), their synonymic series, and word-formation families are analyzed, and a thematic classification of paremias is provided. The comparative analysis reveals universal characteristics, such as labour as the foundation of life, its connection with patience, and the condemnation of laziness, as well as nationally specific features determined by economic lifestyles and religious-ethical traditions. The study demonstrates that in the Russian worldview labour is more often interpreted through the prism of patience and hardship, whereas in the Uzbek worldview it is closely associated with craftsmanship (hunar) and collective mutual assistance (hashar). The findings can be applied in courses on intercultural communication and in teaching Russian and Uzbek as foreign languages.